Strategic Management of Pancasila and Rahmatan Lil’alamin Values in State Islamic Senior High Schools - Herson Anwar; Buhari Luneto; Wiwik Pratiwi; Irawan Irawan; Musthofa Musthofa (Jurnal Ilmiah Peuradeun, 2026)
The implementation of the Project to Strengthen the Pancasila Student Profile and the Rahmatan lil’alamin Profile (P5-PPRA) in State Islamic Senior High Schools (Madrasah Aliyah Negeri) faces persistent managerial challenges despite its strategic role in strengthening student character. This study examined how P5-PPRA has been strategically planned, implemented, and evaluated in Madrasah Aliyah Negeri in Gorontalo Province, with particular attention to supporting and inhibiting factors within an educational management framework. Using a qualitative case study design, data were collected through in-depth interviews with leaders, teachers, students, and stakeholders from the madrasah, supported by observations and document analysis. The validity was ensured by triangulation of sources, methods, and time. The findings demonstrated that P5-PPRA contributed positively to the awareness and enactment of Pancasila values by students and the Islamic principle of Rahmatan lil ‘alamin when embedded in institutional strategic management, curriculum integration, commitment to leadership and teacher facilitation. However, its effectiveness was constrained by limited human resources, inadequate infrastructure, resistance to organizational change, weak inter-institutional collaboration, and the absence of systematic evaluation mechanisms. The study offers a management-oriented paradigm for incorporating civic and religious values in Islamic secondary education by redefining character education as an organizational and managerial process as opposed to a strictly normative or pedagogical aim.